2022
DOI: 10.1177/16878140211070445
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the effect of silver nanoparticles on performance of coconut oil based cutting fluid in minimal fluid application

Abstract: In this work, an innovative nanocutting fluid, based on coconut oil was developed by dispersing silver nanoparticles (AgNPs) of size less than 50 nm. The tribological and physical properties of the prepared nanocutting fluid with different volumes of silver nanoparticles were studied. It was found that the addition of 4% by volume of nanoparticles enhanced the properties of the nanocutting fluid compared to the other concentrations studied, thus demonstrating its excellent tribological performance. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Other researchers have explored the potential of different types of nano-additives, such as silver nanoparticles [41], carbon nanotubes [42], and alumina nanoparticles [43] in enhancing the properties of cutting fluids. These studies have reported improvements in properties such as thermal conductivity, viscosity, and wear resistance.…”
Section: Nano-additives In Cutting Fluidsmentioning
confidence: 99%
“…Other researchers have explored the potential of different types of nano-additives, such as silver nanoparticles [41], carbon nanotubes [42], and alumina nanoparticles [43] in enhancing the properties of cutting fluids. These studies have reported improvements in properties such as thermal conductivity, viscosity, and wear resistance.…”
Section: Nano-additives In Cutting Fluidsmentioning
confidence: 99%